Civil protection in Italy - coping with multiple disasters. Issue 4 (27th November 2018) - Alexander, David
ABSTRACT: In Italy, 2017 was a period of intense natural disasters but also of laboured reforms to the national civil protection system, which was under strain after a series of damaging earthquakes and other extreme events. The 2009 L'Aquila earthquake cast a long shadow in terms of the aftermath of the (ultimately unsuccessful) prosecution of members of the National Major Risks Commission for providing misleading information on seismic risk. The trial involved some serious issues of trust in government and science, but it also stimulated the authorities to look more closely at building public warning systems. Recovery solutions applied to L'Aquila were not followed in the aftermath of the later central Apennine earthquakes, which returned to models that had been current in 1980, particularly those involving growth poles. While emergency response remains Italy's forte, there is little progress in insuring people against natural perils. How to achieve the transition from response to prevention remains a largely unanswered question.